Unveiling the binary nature of NGC 2323 - Qin, Songmei; Zhong, Jing; Tang, Tong; Jiang, Yueyue; Wang, Long; Wu, Kai; Anders, Friedrich; Balaguer-Núñez, Lola; Liu, Guimei; Li, Chunyan; Hou, Jinliang; Chen, Li (Astronomy and astrophysics, 2025)
Context. As a well-known open cluster, NGC 2323 (also called M50) has been widely investigated for over a hundred years and has always been considered a classical single cluster.Aims. We studied the binary structure nature of NGC 2323 with Gaia Data Release 3 (DR3).Methods. We discovered the binary structure of NGC 2323 by the HDBSCAN algorithm based on the astrometric and photometric data from Gaia DR3. Then we employed the PETAR N-body code to investigate its binary structure origin.Results. We found that NGC 2323 consists of two distinct subclusters (NGC 2323-a and NGC 2323-b) that are still gravitationally bound. They have very close positions (three-dimensional Δpos = 12.3 pc, σΔpos = 3.4 pc) and similar tangential velocities (two-dimensional ΔV = 2.2 km s−1, σΔV = 0.02 km s−1). The best isochrone fitting ages of the two clusters are the same (158 Myr), further proving their possibly common origin. The numerical N-body simulation suggests that the less massive cluster is unlikely to be the cluster tidal tails created by the differential rotation of the Milky Way.